2000
DOI: 10.1063/1.481128
|View full text |Cite
|
Sign up to set email alerts
|

Thermal composition fluctuations near the isotropic Lifshitz critical point in a ternary mixture of a homopolymer blend and diblock copolymer

Abstract: We have studied thermal composition fluctuations of a ternary symmetric homopolymer/diblock copolymer system of PEE/PDMS/PEE-PDMS ͓PEE and PDMS being poly͑ethyl ethylene͒ and poly͑dimethyl siloxane͒, respectively͔ in its disordered state with small angle neutron scattering for concentration ⌽ of diblocks up to 15%. The phase diagram shows three characteristic regimes; ͑1͒ below the Lifshitz concentration ⌽ LL Х9%; ͑2͒ in the very near vicinity of the Lifshitz concentration; and ͑3͒ above ⌽ LL . In the regime ͑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 32 publications
8
81
0
Order By: Relevance
“…It is possible that the GµE phase coincides with the "microemulsion" (µE) phase indicated in the experimental phase diagram of Schwahn et al [41]. Strictly speaking, however, the two systems cannot be compared directly to each other, because our simulations were carried out in two dimensions only.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is possible that the GµE phase coincides with the "microemulsion" (µE) phase indicated in the experimental phase diagram of Schwahn et al [41]. Strictly speaking, however, the two systems cannot be compared directly to each other, because our simulations were carried out in two dimensions only.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, they found that dynamic light scattering provided a clear signal for this transition, which they proposed to be the homopolymer/homopolymer Lifshitz line originally introduced by Holyst and Schick [40]. In a similar experimental system, Schwahn et al [41] found evidence for the existence of three different regimes in the disordered phase, a "disordered blend", a "microemulsion", and a "disordered copolymer" region. The three regimes differ from each other by the value of the peak wavevector q * in the structure factor -zero in the disordered blend, large in the disordered copolymer, intermediate in the microemulsion.…”
Section: Introductionmentioning
confidence: 92%
“…Note, that for the polymer blends, [13,14] whose description is the goal of our work, due to the incompressibility condition, the order parameter is a scalar, i. e. n ¼ 1, as is indeed clear from the Hamiltonian (1). The D 1 diagram is q-independent and is therefore of no relevance to the renormalization of c 1 .…”
Section: Perturbative Calculation Of the Shift Of The Lifshitz Linementioning
confidence: 90%
“…We would like to stress that the present study predicts that the LL approaches its mean-field counterpart for high and deep temperatures, the prediction which is also in agreement with experimental behavior of the LL. [13,14] However, on the basis of the current data of ref. [13,14] it is not clear which of three cases concerning the value of the lower critical dimension of the system which we have discussed above actually takes place.…”
mentioning
confidence: 96%
“…Incompatible blends with these macroscopic phase-separated regions often exhibit poor mechanical properties. Considerable attention has been focused on the block copolymer as compatibilizers to increase the miscibility and to control the dispersion within the past decades [4][5][6][7][8][9][10][11]. However, block copolymers are relatively expensive to be synthesized, which limits the practical application of block copolymers as compatibilizer in a large amount.…”
Section: Introductionmentioning
confidence: 99%